Cumulative incidence of venous thromboembolism in patients with advanced cancer in prospective observational study. (9th January 2021) - Kenmotsu, Hirotsugu; Notsu, Akifumi; Mori, Keita; Omori, Shota; Tsushima, Takahiro; Satake, Yasuomi; Miki, Yoshihiro; Abe, Masakazu; Ogiku, Masahito; Nakamura, Toshio; Takagi, Masakazu; Ochiai, Hideto; et al.
Abstract: Venous thromboembolism (VTE) is frequently observed in patients with advanced cancer. The objective of this prospective observational study was to estimate, based on intensive screening, using computed tomography, lower‐extremity ultrasonography, and D‐dimer testing, the prevalence of VTE in patients with advanced cancer. Patients with metastatic or locally advanced cancer without anticoagulant therapy, who were planning to receive chemotherapy during 4 weeks, were eligible. Evaluations of VTE were performed at pretreatment, 12 weeks, and 24 weeks after the start of chemotherapy. Primary endpoint was cumulative incidence of VTE for 24 weeks. Secondary endpoints included incidence of VTE (pretreatment, 12 weeks, and 24 weeks after the start of chemotherapy), VTE according to primary cancer site, symptomatic VTE, pulmonary thromboembolism (PE), and treatment of VTE. We enrolled 860 patients with a median age of 68 years, including 34% female and 71% lung cancer. Cumulative incidence of VTE for 24 weeks was 22.6% (95% confidence interval: 19.8%–25.5%) (194 of 860 patients). Incidence of VTE was 11.3% pretreatment, 16.8% 12 weeks, and 14.1% 24 weeks. Symptomatic VTE was observed in 4.0% and PE in 1.0% of patients. By multivariate analysis, sex, D‐dimer level, and platelet count were independent risk factors of VTE for 24 weeks. This large prospective observational study showed that cumulative incidence of VTE was high in advanced cancer patients, mainly lung cancer. Although most patients showed asymptomatic VTE, intensive screening of VTE may be considered in advanced cancer patients, especially in women with high level of D‐dimer and decreased platelet count (UMIN000015243). Abstract : In 860 patients with advanced cancer, cumulative incidence of VTE for 24 weeks was 22.6% (95% confidence interval: 19.8%–25.5%). Incidence of VTE was 11.3% pretreatment, 16.8% 12 weeks, and 14.1% 24 weeks. By multivariate analysis, sex, D‐dimer level, and platelet count were independent risk factors of VTE for 24 weeks.